The Sanguinaires C shipwreck, Corsica: An early 16th century clinker-built ship of northern origin - Alfonsi, Hervé; Rieth, Eric; Sadania, Marine (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
Discovered in 2005, the Sanguinaires C shipwreck is located near the Sanguinaires Islands in the Gulf of Ajaccio (Corsica). After two surveys, a multiannual program (2021–2023) has been implemented. The wreck is characterized by a stone mound (dolomitic limestone) covering the architectural remains of the hull. A secondary cargo of Pisan and Ligurian ceramics dating from the first part of the 16th century has been discovered. Excavation of the architectural remains, limited to the fore and aft ends of the keel, has brought to light several main features; the most important one, in the Mediterranean context, concerns the clinker structure of the planking.